1998
DOI: 10.1097/00005053-199807000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Insight and Interpersonal Function in Schizophrenia

Abstract: Research has linked impaired insight in schizophrenia to poorer medication compliance and treatment outcome. It is unclear, however, whether poorer interpersonal function is also associated with impaired insight. To examine this question, subjects with schizophrenia or schizoaffective disorder were classified as having unimpaired (N = 44) or impaired (N = 57) insight, and their scores on Heinrichs et al.'s Quality of Life (QOL) Scale were compared. Multiple regressions were conducted to determine the relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
50
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(64 citation statements)
references
References 26 publications
11
50
0
3
Order By: Relevance
“…Se pueden utilizar períodos de tiempo más cortos o más largos para la valoración actual y retrospectiva de la conciencia y la atribución, dependiendo de los objetivos de la investigación. En los síntomas ítems (números [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] se debe valorar la comprensión del sujeto acerca de la causa de su síntoma (la atribución).…”
Section: Instruccionesunclassified
“…Se pueden utilizar períodos de tiempo más cortos o más largos para la valoración actual y retrospectiva de la conciencia y la atribución, dependiendo de los objetivos de la investigación. En los síntomas ítems (números [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] se debe valorar la comprensión del sujeto acerca de la causa de su síntoma (la atribución).…”
Section: Instruccionesunclassified
“…Post hoc analyses showed that reduction of insight-linked hopelessness might have accounted for the positive effect of CBSST on functioning compared with TAU. These findings along with prior research on the relationship between insight and hopelessness and depression [1,3] suggest that hopelessness may be an important clinical target in CBT for schizophrenia.…”
Section: Discussionmentioning
confidence: 58%
“…Given the established relationship between high insight and depression in people with schizophrenia [1,3], we conducted post hoc Chi-square and correlation analyses to explore the hypothesis that CBSST might have reduced the negative impact of insight-linked hopelessness on functioning compared with TAU, thus contributing to the moderation effect just described. In the total sample, greater insight (BIS) at follow-up was not significantly correlated with HAM-D total scores (r = 0.19, p = 0.15, n = 62), but was significantly correlated with greater hopelessness at follow-up (Spearman rank correlation r = 0.26, p = 0.04, n = 61).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations